Problematika Hukum dalam Produktifitas Aset Wakaf (Studi Kasus Masjid Rahmat Kembang Kuning Surabaya) - Achmad Siddiq (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The presence of Law Number 41 of 2004 concerning Waqf which brings the paradigm of productive waqf management is a challenge for classic waqf institutions which have so far been dominated by forms of waqf in the form of mosques, prayer rooms and cemeteries. Classical waqf, which has so far been self-sufficient on the development of ubûdiyyah values, is required to develop itself as a waqf institution that has a socio-economic dimension in order to participate in the welfare of its people. As a consequence, these classic waqf institutions must utilize their assets to produce something that can support their own operations as well as having added value that can improve the welfare of their community. The Rahmat Kembang Kuning Mosque in Surabaya has responded to the productive waqf management paradigm by carrying out various utilization of assets owned, including land swaps, land leasing, business cooperation, tower construction cooperation, establishment of da'wah radio and education. From a juridical perspective, efforts to increase the productivity of waqf assets do not have significant problems, but managerially they encounter obstacles that lead to Nazhir's professionalism. Even so, the management of the Rahmat Mosque can be seen as productive as a waqf institution that is engaged in ubûdiyyah as its main priority scale and has tried to develop asset utilization so that it has socio-economic and cultural values as a scale of support for the waqf institution